Rising atmospheric CO2 reduces nitrogen availability in boreal forests - Kelley R. Bassett; Stefan F. Hupperts; Sandra Jämtgård; Lars Östlund; Jonas Fridman; Steven S. Perakis; Michael J. Gundale (Nature, 2026)
Abstract Anthropogenic nitrogen (N) pollution is a cause of eutrophication globally 1 . However, recent datasets indicate that some ecosystems may be experiencing widespread oligotrophication—declining N availability—which is suggested to be a response to elevated atmospheric carbon dioxide (CO 2 ) 2 . Plant N isotope (δ 15 N) chronologies have served as primary evidence for oligotrophication, but there is wide disagreement whether rising CO 2 or temporal changes in N deposition explain these patterns 3–6 . Here we construct δ 15 N tree-ring chronologies using archived samples from Sweden’s 23.5-million-hectare forest area from 1961 to 2018. The study area spans a 1,500-km latitudinal distance where N deposition varies fourfold, but where rising CO 2 is spatially uniform. Our data show declining δ 15 N chronologies throughout Sweden, including forests in the far north where atmospheric N deposition rates are very low. Linear mixed-effects models showed that rising CO 2 is the strongest predictor of δ 15 N values, whereas N deposition variables, temperature and forest basal area had lower explanatory power. Our findings suggest that elevated atmospheric CO 2 is causing oligotrophication in boreal forests, which has implications for predicting their future role as sinks in the global carbon cycle 7–9 .